Analisa Pengaruh Desain Motor Induksi “6 Fasa 2 Lapis Tak Simetris” Terhadap Torsi Dan Kecepatan Motor Induksi 3 Fasa Menggunakan Metode Elemen Hingga - Jourdan Imran Simanjuntak; Zuriman Anthony; Sepannur bandri; Anggun Anugrah (STEKOM PRESS, 2024)
Induction motors are components that convert electrical energy into mechanical energy and are very much in demand among industries, with low prices, sturdy construction and easy maintenance making these induction motors used for heavy industrial applications. However, the 3-phase induction motor at this time chooses a low torque and speed so that it affects the efficiency of the induction motor performance, which will decrease. This study examines the effect of unsymmetrical 2-layer 6-phase induction motor design on the torque and speed of 3-phase induction motors using the finite element method. This research was conducted using Ansys software, which aims to see the magnetic flux density and the effect of 6-phase induction motor design on the torque and speed of a 3-phase induction motor using the finite element method. The induction motor that is the reference for this research has specifications of a 3-phase induction motor: 0.75 KW, 1 HP, 220/380 V, 3.5/2 A, 50 Hz, 1390 rpm. From the results of this study, the simulation results of the shape of the flux density ... which is designed with the parameters of a 3-phase induction motor with an unsymmetrical 6-phase 2-layer induction motor coil design.